2023
DOI: 10.3390/jof9010127
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Supernatant of Bacillus subtilis Reduces Kiwifruit Rot Caused by Botryosphaeria dothidea through Inducing Oxidative Stress in the Pathogen

Abstract: Biological control of postharvest diseases has been proven to be an effective alternative to chemical control. As an environmentally friendly biocontrol agent, Bacillus subtilis has been widely applied. This study explores its application in kiwifruit soft rot and reveals the corresponding mechanisms. Treatment with cell-free supernatant (CFS) of Bacillus subtilis BS-1 significantly inhibits the mycelial growth of the pathogen Botryosphaeria dothidea and attenuates the pathogenicity on kiwifruit in a concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Pot experiments revealed that CLPs, similar to their source B. amyloliquefaciens DHA6 [19], possess significant potential in promoting plant growth and suppressing Fusarium wilt in watermelon (Figure 3), indicating that the production of CLPs is a prominent mechanism of B. amyloliquefaciens DHA6 involved in plant growth promotion and biocontrol of Fusarium wilt. Similarly, previous studies have demonstrated that iturin A-and surfactin A-enriched CLPs derived from B. subtilis BS-1 and B. amyloliquefaciens S76-3 have been shown to suppress kiwifruit rot (Botryosphaeria dothidea), rice bakanae disease (Fusarium moniliforme), wheat head scab (Fusarium graminearum), and lettuce Fusarium wilt [47,[60][61][62]. Thus, antagonistic bacteria employ different antimicrobial CLPs as a primary mechanism for the biocontrol of crop diseases [16].…”
Section: Discussionmentioning
confidence: 77%
“…Pot experiments revealed that CLPs, similar to their source B. amyloliquefaciens DHA6 [19], possess significant potential in promoting plant growth and suppressing Fusarium wilt in watermelon (Figure 3), indicating that the production of CLPs is a prominent mechanism of B. amyloliquefaciens DHA6 involved in plant growth promotion and biocontrol of Fusarium wilt. Similarly, previous studies have demonstrated that iturin A-and surfactin A-enriched CLPs derived from B. subtilis BS-1 and B. amyloliquefaciens S76-3 have been shown to suppress kiwifruit rot (Botryosphaeria dothidea), rice bakanae disease (Fusarium moniliforme), wheat head scab (Fusarium graminearum), and lettuce Fusarium wilt [47,[60][61][62]. Thus, antagonistic bacteria employ different antimicrobial CLPs as a primary mechanism for the biocontrol of crop diseases [16].…”
Section: Discussionmentioning
confidence: 77%
“…Fresh mycelia of G1H were treated with 0, 5, 10%, or 15% WJ561 CFS at 25°C for 24 h. The treated mycelia were filtered and fixed with 2.5% glutaraldehyde for 24 h. This was followed by dehydration with graded ethanol (30, 50, 70, and 90%, v/v) as described ( Fan et al, 2023 ). The dried samples were coated with gold and subsequently observed using scanning electron microscopy (SEM, Hitachi Regulus 8,220, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The MDA content was determined using a commercial thiobarbituric acid (TBA) kit (Bioroyee (Beijing) Biotechnology Co., Ltd., Beijing, China). The filtrated solutions were used for the determination of nucleic acid and soluble protein exudation via the NanoDrop One (Thermo Fisher Scientific, Waltham, MA, United States), as described previously with some modifications ( Cai et al, 2015 ; Fan et al, 2023 ). Each treatment consisted of three biological replicates, and the experiments were performed three times.…”
Section: Methodsmentioning
confidence: 99%
“…15 In addition, several bacterial strains from the genus Bacillus, Streptomyces, Pseudomonas and Xenorhabdus have demonstrated, alone or in combination with other BCAs, their antagonism against Botryosphaeriaceae species in several crops. 38,40,[44][45][46][47][48][49][50][51][52] Rhizospheric bacteria have been demonstrated as potential biocontrol agents of the soil-borne pathogen M. phaseolina within the Botryosphaeriaceae family in strawberry crops. 53,54 However, to the best of our knowledge, no control agents based on bacterial strains have been successfully tested against canker diseases caused by Botryosphaeriaceae in almond.…”
Section: Introductionmentioning
confidence: 99%
“…atroviride SC1 has been registered in California as a biological control agent against almond canker pathogens 15 . In addition, several bacterial strains from the genus Bacillus , Streptomyces , Pseudomonas and Xenorhabdus have demonstrated, alone or in combination with other BCAs, their antagonism against Botryosphaeriaceae species in several crops 38,40,44–52 . Rhizospheric bacteria have been demonstrated as potential biocontrol agents of the soil‐borne pathogen M .…”
Section: Introductionmentioning
confidence: 99%